Physiological and pathological characteristics of vascular endothelial injury in diabetes and the regulatory mechanism of autophagy - Liu, Hanyu; Wang, Xueru; Gao, Hong; Yang, Chan; Xie, Chunguang (Frontiers in Endocrinology, 2023)
Vascular endothelial injury in diabetes is the primary link of vascular disease, which is closely related to the occurrence and development of a series of vascular complications, and has a serious negative impact on patients' health and quality of life. The core function of normal vascular endothelium is to play a barrier function, but in the state of diabetes, glucose and lipid metabolism disorder, insulin resistance, inflammatory reaction, oxidative stress and other factors cause vascular endothelial injury, leading to vascular endothelial lesions from morphology to function. In recent years, more and more studies have found that autophagy plays an important role in regulating the progress of vascular endothelial injury. Therefore, this article compares the morphology and function of normal and diabetic vascular endothelium, and focuses on the current regulatory mechanism and important role of autophagy in diabetes vascular endothelial injury from different signal pathways. It is hoped to provide some references for the further researches on the mechanism of vascular endothelial injury in diabetes, exploring the threshold of autophagy's protective or injurious effect, and studying potential drugs with autophagy as a target in the future.